Standardization of sample collection, isolation and analysis methods in extracellular vesicle research. Issue 1 (27th May 2013) - Witwer, Kenneth W.; Buzás, Edit I.; Bemis, Lynne T.; Bora, Adriana; Lässer, Cecilia; Lötvall, Jan; Nolte‐'t Hoen, Esther N.; Piper, Melissa G.; Sivaraman, Sarada; Skog, Johan; Théry, Clotilde; Wauben, Marca H.; et al.
Abstract : The emergence of publications on extracellular RNA (exRNA) and extracellular vesicles (EV) has highlighted the potential of these molecules and vehicles as biomarkers of disease and therapeutic targets. These findings have created a paradigm shift, most prominently in the field of oncology, prompting expanded interest in the field and dedication of funds for EV research. At the same time, understanding of EV subtypes, biogenesis, cargo and mechanisms of shuttling remains incomplete. The techniques that can be harnessed to address the many gaps in our current knowledge were the subject of a special workshop of the International Society for Extracellular Vesicles (ISEV) in New York City in October 2012. As part of the "ISEV Research Seminar: Analysis and Function of RNA in Extracellular Vesicles (evRNA)", 6 round‐table discussions were held to provide an evidence‐based framework for isolation and analysis of EV, purification and analysis of associated RNA molecules, and molecular engineering of EV for therapeutic intervention. This article arises from the discussion of EV isolation and analysis at that meeting. The conclusions of the round table are supplemented with a review of published materials and our experience. Controversies and outstanding questions are identified that may inform future research and funding priorities. While we emphasize the need for standardization of specimen handling, appropriate normative controls, and isolation and analysis techniques to facilitate comparison of results, we also recognize that continual development and evaluation of techniques will be necessary as new knowledge is amassed. On many points, consensus has not yet been achieved and must be built through the reporting of well‐controlled experiments.